LEADERSHIP BEHAVIOR AND OUTCOME OF COMMERICIAL AND THRIFT BANKS IN SILANG, CAVITE: A PERFORMANCE ANALYSIS - Hutabarat, Francis (Jurnal Ekonomis, 2010)
The study analyze the management leadership behaviors of selected commercial and thrift banks in Silang, Cavite, and find out their dependency with the related leadership outcome based on the theoretical framework of the study. The study employs a descriptive method of research that seeks to analyze several bank management teams’ leadership behaviors as perceived by the employees and their leadership outcomes, as conceptualized by the Blake and Mouton Managerial Grid Theory. The leadership behavior are listed as impoverished management (1,1), country club management (1,9), middle-of-the-road management (5,5), produce-or-perish management (9,1) or team management (9,9). Procedures in plotting the behavior originate from the overall means of respondents’ perception on concern for task and people. The demographic profile indicated that respondents of the study were mostly female with an age bracket of 21 to 40 who were married and bachelor’s degree holders. About 91% of them were regular employees who have been working for the banks for a period of more than 11 years. The findings of the study were as follows: The leadership behavior identified in all commercial and thrift banks in Silang to be Team Management according to Blake and Mouton Managerial Grid Theory. There were also no significant differences in the perception of the banks support staff and also management on concern for task and people when they were grouped by demographic variables such as: gender, age, marital status, highest level of education, employment status, and length of service. The differences seen are in the following: performing task efficiently and pinpointing weaknesses, and for concern for people: honoring other’s feeling and accommodating ideas. There were significant correlations between leadership behavior and outcome for concern for task except for a few variables. Keyword: Leadership behavior, leadership outcome, concern for task, concern for people